Novel Technique in Performing Standard Transperineal Template Prostate Biopsies Under Local Anaesthetic - Nafie, Sahdy; Berridge, Christopher; Khan, Masood Ahmed (Urology Journal, 2022)
Purpose: Transperineal template prostate biopsies (TPTPB) are now increasingly commonly performed for the diagnosis of prostate cancer. TPTPB are traditionally performed under general anaesthetic. However, this poses a significant strain on hospital theatre capacity. As such, local anaesthetic (LA) TPTPB are becoming more popular. We describe a novel technique in performing the standard TPTPB under LA in the outpatient setting. Materials and Methods: Between February 2019- February 2021, 254 consecutive men (median age 69; range: 44-80 years) with a median PSA of 8.7 ng/ml (range: 2.2-76) underwent L/A TPTPB using our novel technique. This is whereby 50mls of 1% prilocaine was injected partially around the perineal skin and partially deep bilateral periprostatic areas. Multiple simultaneous prostate biopsies were then taken with the standard template grid and stepper. Results: A total of 250/254 (98.4%) men underwent successful L/A TPTPB with a median visual analogue pain score of 4 (range: 2-8). The median prostate volume was 49cc (range: 14-240cc). The median number of cores taken were 18 (range: 14-24). A total of 163/250 men (65.2%) had a positive histology for prostate cancer with a median of 5 cores being involved with prostate cancer (range: 1-18). In addition, 101/163 men (62.0%) diagnosed with prostate cancer had either Gleason score 3+4=7 or greater. None experienced urosepsis and only 2/250 men (0.8%) had temporary urinary retention. Conclusion: Our novel LA technique in performing the standard TPTPB is safe, feasible and well tolerated and associated with a high rate of prostate cancer detection.